Speciation in three-spined stickleback - Dean, Laura L. (2018)
Speciation, the division of one species into two, has provided evolutionary biologists with a rich ensemble of questions, conundrums and revelations for over a century, and yet our understanding of many of the factors affecting this complex, multidimensional process remains limited. In this thesis, I aimed to further our understanding of speciation using divergent populations of three-spined stickleback (Gasterosteus aculeatus) on the island of North Uist, Scottish Western Isles. Firstly, I explored the degree of morphological and genetic separation between three stickleback ecotypes, showing that both strongly reproductively isolated, and admixed populations exist in close proximity. I then attempted to identify the ecological and genetic origins of strongly isolated species-pairs, testing two competing explanations for their existence. I showed that a recent ‘double-invasion’ is unlikely, but found stark differences in the long-term genetic history between ecotypes, indicating that the evolution of species-pairs may be related to secondary contact between anciently diverged mitochondrial lineages. I then conducted mate choice trials to assess mating preferences between ecotypes, and to test for reinforcement in species-pairs. Consistent with the idea that speciation in this case is not driven purely by ecological factors, I found no evidence that reinforcement drives assortative mating in species-pairs. Rather, it appears that extant mating preferences have developed as a by-product of other adaptations. Finally, I took a brief interlude to document and investigate an exciting chance finding, internally developed embryos retained within the ovaries of a normally oviparous species, before concluding by summing up my findings, their relevance for scientific progress, and avenues opened up for further research.